Audit Quality Determinants and Their Influence on Financial Reporting Reliability (gjstudies, 2020)
This research paper investigates the multifaceted determinants of audit quality and theirsubsequent influence on the reliability of financial reporting, proposing a novel, integratedframework that diverges from traditional, siloed approaches. While prior literature has examined individual factors such as auditor independence, expertise, or firm size, this studyuniquely synthesizes these elements with under-explored dimensions including cognitive biases in audit judgment, the role of organizational culture within audit firms, and the impactof emerging, non-financial information assurance. The central research question addresseshow an interconnected system of technical, behavioral, and institutional determinants collectively shapes audit outcomes, moving beyond linear cause-effect models. Methodologically,the paper employs a mixed-methods design, combining a longitudinal analysis of archivalaudit failure data from 1995 to 2004 with a qualitative, grounded theory analysis of in-depthinterviews with audit partners and technical reviewers. This approach allows for the identification of latent patterns and interactive effects not captured by standard regression models.The results reveal a critical, non-linear relationship between determinants; for instance, hightechnical expertise can be negated by a pervasive culture of commercialism within the auditfirm, and formal independence safeguards are often subverted by subtle, relational biases.A key novel finding is the identification of ’assurance elasticity’—a threshold effect whereincremental improvements in individual determinants yield diminishing returns on reportingreliability until a systemic, holistic enhancement is achieved. The conclusion argues for aparadigm shift in audit regulation and firm management towards integrated quality ecosystems, emphasizing that the reliability of financial statements is not a product of isolatedinputs but of their complex, synergistic interaction. This research contributes original insights by reframing audit quality as a dynamic, systemic property, offering a new theoreticallens and practical implications for standards setters, audit firms, and corporate governancebodies seeking to enhance trust in financial markets